SUMBER DAYA GURU DALAM IMPLEMENTASI KEBIJAKAN KARAKTER DI SEKOLAH SMPN 1 PLOSOKLATEN KEDIRI - Iis Maulah (Khazanah Pendidikan, 2018)
One of the great challenges that must be faced and soon resolved in Indonesia isthe character of the learner. Therefore, school education has an important rolein building the character of students in Indonesia. This study aims to determinethe teacher resources in the implementation of character education policy inSMPN 1 Plosoklaten. This research is a qualitative research with case studyapproach. The results of this study indicate that the existing teacher resources inPlosoklaten still require guidance and supervision, because the implementationof the policy listed in Permendikbud No. 23 2016 still as a formality, so thecharacter of students in SMPN 1 Plosoklaten still not maximal.Keywords: teacher resources, policy implementation, character education